Stakeholder Perspectives on the Role of Peer Mentors in the Implementation of Long-Acting Antiretroviral Therapy for Use by Adolescents and Young People in Western Kenya: Findings from a Formative Study, KuwaFree! LiveFree! - Salim Bakari DipPsych; Biegon Whitney DipPsych; Munyoro Dennis Cert; Shukri Hassan MPHc; Caitlin Bernard MD, MSCI; Eunice Kaguiri BSc, MPH; Mehar Maju MDc; Edith Apondi MMED; Edwin Were MD, MBChB (O/G), MPH; Rena C. Patel MD, MPH, MPhil (Journal of the International Association of Providers of AIDS Care)
Long-acting antiretroviral treatment (LA ART) is a forthcoming option for adolescents and young people living with HIV (AYPLHIV), but perspectives on using peer mentors to implement LA ART for AYPLHIV are unknown. We conducted seven focus group discussions ( n  = 58 participants) from November 2021 to April 2022 in Kenya with four stakeholder groups, including AYPLHIV, healthcare providers, advocates, and policymakers. We used inductive coding and thematic analysis. Our stakeholders articulated peer mentors are crucial in the implementation of LA ART for AYPLHIV in leading communication, facilitating referrals, and providing empathy from lived experiences. Additionally, they can serve as early adopters, help navigate service points, and provide messaging on the benefits and drawbacks of LA ART. They emphasized the necessity of training peer mentors for the LA ART scale-up. Peer mentors are essential for linkage and referring of AYPLHIV to LA ART, and peer mentors' involvement should be integrated into a national implementation plan.